Acute effects of blood transfusion on growth hormone and insulin-like growth factor-1 levels in children with thalassemia - Pat Mahachoklertwattana (2018)
Background/Aim: Children with β-thalassemia have chronic anemia and growth retardation. Impaired growth hormone (GH)-insulin-like growth factor-1 (IGF-1) axis function has been demonstrated. Growth improvement has been demonstrated following optimal blood transfusion. Whether correction of anemia by blood transfusion augments GH-IGF-1 axis function has not been established. Methods: Twenty children with thalassemia aged 11.7 years (5.3-16.3 years) were recruited. GH provocative tests were performed twice, before and 1 week after blood transfusion. IGF-1, IGF-binding protein-3 (IGFBP-3) and hematocrit were measured. Results: Median IGF-1 and IGFBP-3 concentrations were significantly increased at 1 week following transfusion: pre- versus posttransfused concentrations: 86.4 versus 143.5 ng/ml (p < 0.001) and 2.95 versus 3.75 mg/l (p < 0.001), respectively. However, median peak GH levels and areas under the curve of GH during GH testing between pre- and posttransfusion periods were not different. The pretransfused hematocrit level was correlated with pretransfused IGF-1 (r = 0.662, p < 0.001) and IGFBP-3 (r = 0.691, p < 0.001) levels. Conclusions: In thalassemics, correction of anemia by blood transfusion rapidly enhanced GH-mediated IGF-1 and IGFBP-3 secretion. This suggests thatanemia may be one of the factors causing partial GH insensitivity. Copyright © 2010 S. Karger AG, Basel.